The development of speed abilities at the beginners track-and-field athletes aged 11–14 with different physique - Артюшенко [Aleksandr Artyushenko] Олександр Федорович (Slobozhanskyi Herald of Science and Sport, 2012)
<!–[if gte mso 9]> Normal 0 false false false <![endif]–> The goal of the research is to find out the most favourable age periods for the development of speed-strength abilities at the boys aged 11–14 with different physique. The typological groups of the boys were distinguished according to the total body sizes. The comparative analysis of speed-strength preparedness level of the boys aged 11–14 was conducted; conventionally referred to four groups. The boys of different typological groups were found to differ significantly according to the level of speed-strength abilities. The value of index growth of speed-strength abilities at the boys aged 11–14 of different somatic types was found to differ significantly in the result of short standard training program of sprint focus. The age periods with relatively high and low growth level were distinguished. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>